Violent crime redistribution in a city following a substantial increase in the number of off‐sale alcohol outlets: A Bayesian analysis. (22nd November 2017) - Gorman, Dennis M.; Ponicki, William R.; Zheng, Qi; Han, Daikwon; Gruenewald, Paul J.; Gaidus, Andrew J.
Abstract: Introduction and Aims: This study examined whether the introduction of a large number of off‐premise alcohol outlets into a city over a brief period of time could affect rates of violent crime. Design and Methods: The study analysed annual counts of violent crime across 172 US Census block groups in Lubbock, Texas from 2006 through 2011. Spatial Poisson models related annual violent crime counts within each block group to off‐premise and on‐premise alcohol outlets active during this time period as well as neighbourhood socio‐demographic characteristics. The effects of alcohol outlets were assessed both within block groups and across adjacent block groups. Results: On‐premise outlets had a small, significant positive association with violence within a given block group. A similar well‐supported local effect for off‐premise outlets was not found. However, the spatially lagged effect for off‐sale premises was well‐supported, indicating that greater densities of these outlets were related to greater rates of violent crime in adjacent areas. Discussion and Conclusions: While these analyses confirmed a previous time‐series analysis in finding no city‐wide effect of the increase in off‐premise outlets, they do suggest that such outlets in a local area may be related to violence in nearby geographic areas. They indicate the importance of examining neighbourhood‐specific effects of alcohol outlets on violence in addition to the city‐wide effects. They also present further evidence supporting the need to examine the differential effects of on‐sale and off‐sale premises.